Status Kepemilikan Satuan Rumah Susun Oleh Orang Asing Di Indonesia Dan Singapura - Siti Nurjanah; Gusita Christa (Journal of Judicial Review, 2015)
Indonesia and Singapore, the two countries are quite attractive to foreign investors, as an ideal choice to invest in property. Indonesia and Singapore, which although the government open up opportunities in foreign ownership of property, but there are also still limited and have restriction by existing regulations. Thus, it doesn’t means chance of foreigners to have property are closed at all. Considering type of property with the ownership status can be granted to foreigners is limited, one of them which is flat unit. Therefore, to avoid misunderstanding to the limitations of the type of property, especially flat unit and ownership that can be owned by foreigners and provide legal certainty for foreigners who want to buy a flat unit in Indonesia and/or Singapore, so it is important to do research particulary regarding to the ownership status on flat unit by foreigners in Indonesia and Singapore.This research is a normative law research or known as normative juridical research be based on comparative law. Data used in this research is secondary data which includes primary legal materials, secondary, and tertiary. With data collection techniques using literature study mode, then the collected data was analyzed by descriptive qualitative analysis.The research obtained results that there are differences over the status of ownership of flat unit by foreigners in Indonesia and Singapore. Viewed from ownership of flat unit by foreigners in Indonesia and Singapore, ownership in Indonesia is more limited than Singapore which not too restricted in ownership of flat unit by foreigners.